Blood pressure trajectories during pregnancy and associations with adverse birth outcomes among HIV-infected and HIV-uninfected women in South Africa: a group-based trajectory modelling approach - Thokozile R. Malaba; Annibale Cois; Hlengiwe P. Madlala; Mushi Matjila; Landon Myer; Marie-Louise Newell; for the PIMS Study Group (BMC, 2020)
Abstract Background High blood pressure (BP) late in pregnancy is associated with preterm delivery (PTD); BP has also been associated with HIV and antiretroviral therapy (ART), but whether the relationship between BP assessed longitudinally over pregnancy and PTD and low birthweight (LBW) is modified by HIV/ART is unclear. We hypothesise the presence of distinctive BP trajectories and their association with adverse birth outcomes may be mediated by HIV/ART status. Methods We recruited pregnant women at a large primary care facility in Cape Town. BP was measured throughout pregnancy using automated monitors. Group-based trajectory modelling in women with ≥3 BP measurements identified distinct joint systolic and diastolic BP trajectory groups. Multinomial regression assessed BP trajectory group associations with HIV/ART status, and Poisson regression with robust error variance was used to assess risk of PTD and LBW. Results Of the 1583 women in this analysis, 37% were HIV-infected. Seven joint trajectory group combinations were identified, which were categorised as normal (50%), low normal (25%), high normal (20%), and abnormal (5%). A higher proportion of women in the low normal group were HIV-infected than HIV-uninfected (28% vs. 23%), however differences were not statistically significant (RR 1.27, 95% CI 0.98-1.63, reference category: normal). In multivariable analyses, low normal trajectory (aRR0.59, 0.41-0.85) was associated with decreased risk of PTD, while high normal (aRR1.48, 1.12-1.95) and abnormal trajectories (aRR3.18, 2.32-4.37) were associated with increased risk of PTD, and abnormal with increased risk of LBW (RR2.81, 1.90-4.15). Conclusions While HIV/ART did not appear to mediate the BP trajectories and adverse birth outcomes association, they did provide more detailed insights into the relationship between BP, PTD and LBW for HIV-infected and uninfected women.